2016
DOI: 10.1016/j.neubiorev.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroanatomy of meditation: A review and meta-analysis of 78 functional neuroimaging investigations

Abstract: Meditation is a family of mental practices that encompasses a wide array of techniques employing distinctive mental strategies. We systematically reviewed 78 functional neuroimaging (fMRI and PET) studies of meditation, and used activation likelihood estimation to meta-analyze 257 peak foci from 31 experiments involving 527 participants. We found reliably dissociable patterns of brain activation and deactivation for four common styles of meditation (focused attention, mantra recitation, open monitoring, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
390
2
17

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 494 publications
(421 citation statements)
references
References 156 publications
12
390
2
17
Order By: Relevance
“…Interoceptive and auditory information represented in the posterior insula is hierarchically rerepresented in the mid-insula and ultimately the anterior insula as it is progressively integrated with sensory, social, and emotional information (Craig 2011). The insula is consistently activated by various forms of meditation (Fox et al 2016), and mindfulness training has been shown to elicit changes in posterior insula function (Farb et al 2007;Burton 2009). Farb et al (2012 demonstrated that daily compliance with an 8-week Mindfulness-Based Stress Reduction (MBSR) program (Kabat-Zinn 1990) was associated with increased posterior insula activation during an interoceptive attention task.…”
Section: Cortical Thickness Changes In the Posterior Insulamentioning
confidence: 99%
See 1 more Smart Citation
“…Interoceptive and auditory information represented in the posterior insula is hierarchically rerepresented in the mid-insula and ultimately the anterior insula as it is progressively integrated with sensory, social, and emotional information (Craig 2011). The insula is consistently activated by various forms of meditation (Fox et al 2016), and mindfulness training has been shown to elicit changes in posterior insula function (Farb et al 2007;Burton 2009). Farb et al (2012 demonstrated that daily compliance with an 8-week Mindfulness-Based Stress Reduction (MBSR) program (Kabat-Zinn 1990) was associated with increased posterior insula activation during an interoceptive attention task.…”
Section: Cortical Thickness Changes In the Posterior Insulamentioning
confidence: 99%
“…Changes in cortical thickness of the posterior insula may lead to changes in auditory processing, and the posterior insula may interact with other regions implicated in auditory processing, such as the left middle/superior temporal gyrus (MTG/STG) and right ventrolateral prefrontal cortex (vlPFC) in a network involved in the detection of novel auditory information (Petrides & Pandya 2002;Plakke & Romanski 2014;Rauschecker & Scott 2009;Schönwiesner et al 2007;Buse & Roessner 2016;Kiehl, Laurens, Duty, Forster, & Liddle 2001). Various forms of meditation are associated with activity in the insula as well as somatomotor cortex, the primary cortical site of tactile information processing (Fox et al 2016). A meta-analysis by Fox et al (2014) also points to altered somatomotor cortex structure among long-term meditation practitioners compared to controls, and a correlational study of Zen meditators showed a correlation between hours of meditation experience and gray matter in primary somatosensory cortex (Grant, Courtemanche, Duerden, Duncan, & Rainville 2010).…”
mentioning
confidence: 99%
“…The field of military medicine has recently recommended MT's use as adjunctive care for servicemembers and veterans suffering from insomnia, PTSD, and chronic pain (Khusid 2013;Khusid andVythilingam 2016a, Khusid andVythilingam 2016b). In addition to recent clinical interest in MT, a literature on MT's neural effects has emerged (see Fox et al 2014Fox et al , 2016. Theoretical accounts suggest that the health-related benefits and neural correlates of MT are tied to functional improvements in cognitive processing that result from regular engagement in MT practices (Creswell 2017;Goldin and Gross 2010;Lutz et al 2015).…”
mentioning
confidence: 99%
“…Depending on the practice and personal context, mantra could be considered an instrument of thought, mind protection, a song of praise, a prayer, or even a sacred incantation. In our case, in a brief course taught to secular novice participants, mantra has fewer of these religious associations and greater similarity to an Binstrument of thought^or as a general form of focused attention with a linguistic component (Fox et al 2016).…”
Section: Introductionmentioning
confidence: 69%
“…Despite appearances, a majority of meditative practices employ very specific techniques to engage and train the mind and body (Manna et al 2010). Western categorization of these techniques, based on their objective aims, has resulted in the subgrouping of practices across traditions such as: focused attention (FA), open monitoring (OM), loving kindness (LM), and mantra (MR) (Lutz et al 2008b;Fox et al 2016). A combination of these and other methods are often practiced in a single sitting.…”
Section: Introductionmentioning
confidence: 99%